Pengaruh Media Kupin untuk Meningkatkan Motivasi dalam Pembelajaran IPAS Berdasarkan Kurikulum Merdeka di Tingkat Sekolah Dasar - Tia Latifatu Sadiah; Maman Faturrohman; Suroso Mukti Leksono; Yulistina Nur DS; Depi Prihamdani (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to determine the effect of Kupin media on increasing student learning motivation in Natural and Social Sciences (IPAS) subjects at the elementary school level, especially grade IV. The method used is quasi-experiment with RND approach, the respondents used are 25 students. Data were collected through observation of motivation and distribution of questionnaires questionnaire learning motivation before and after the use of Kupin media. The findings showed that the average score of students' motivation increased from 60.4 before using Kupin media to 78.2 after using it. This study shows that Kupin media is effective in increasing students' motivation in IPAS lessons. Therefore, it is recommended that Kupin media can be used gradually in the learning process to improve students' motivation and learning outcomes.